2000
DOI: 10.1016/s0920-5632(00)00621-6
|View full text |Cite
|
Sign up to set email alerts
|

Top quark production near threshold

Abstract: The present theoretical status of top quark pair production near threshold at (future) e + e − (µ + µ − ) colliders is summarized.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The t t background sample is also generated with pythia [24], with W bosons and τ leptons forced to leptonic decays, but with b quarks left to decay freely. Both gluon fusion and quark annihilation initial states are simulated and the cross-section is normalised to the NLO value of 840 ± 5%(scale) ± 3%(PDF) pb [45].…”
Section: Datasets For Signal and Background Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The t t background sample is also generated with pythia [24], with W bosons and τ leptons forced to leptonic decays, but with b quarks left to decay freely. Both gluon fusion and quark annihilation initial states are simulated and the cross-section is normalised to the NLO value of 840 ± 5%(scale) ± 3%(PDF) pb [45].…”
Section: Datasets For Signal and Background Processesmentioning
confidence: 99%
“…The following sources of systematic uncertainty are common for all three channels: (i) the theoretical errors to the total rates of the signal is th ≈ 4%, rising to 10% for t W . The uncertainties in the background events are assumed to be: 5% for tt [45], 17% for W bb j, 7% for W + jets, 5% for W j j [319], and 5% for W bb. (ii) the jet energy scale (JES) uncertainty: using a calibration method based on tt events [320], the JES uncertainty after 10 fb −1 integrated luminosity is expected to be ±5% (±2.5%) for jets with p T ≈ 20 GeV/c ( p T > 50 GeV/c).…”
Section: Systematic Uncertaintiesmentioning
confidence: 99%
“…Here we focus on a different issue, non-resonant production of the physical final state after top decay, which though known for some time (see, e.g., the discussion in [29]) has been left aside up to now. The top quark is unstable with a significant width Γ t of about 1.5 GeV due to the electroweak interaction.…”
Section: Introductionmentioning
confidence: 99%
“…However, since t m t , the narrow width approximation approach is valid for t and t quarks. Using this method, it has been shown that the best way to analyse the t t correlation is through angular correlation among the two charged leptons l and l in the di-lepton final state [19]. To obtain the differential cross section of the process e − e + → t t → b lν l bl ν l , the production and decay spin density matrices are written as the usual approach.…”
Section: The Non-universal Gauge Boson Z and The T T Spin Correlation...mentioning
confidence: 99%
“…The coefficients B 1 (B 2 ) and C are related to the mean t ( t) polarization and spin correlation projected into the direction of the spin axis. The spin correlation coefficient C can be written as C = αlα l s t st , (19) where α i is the spin analysing power of particle i, which has opposite signs for the charged leptons l and l. At the leading order, there are αl = −α l = −1.…”
Section: The Non-universal Gauge Boson Z and The T T Spin Correlation...mentioning
confidence: 99%